Apakah Motivasi Berprestasi Dapat Memprediksi Social Loafing Pada Penugasan Kelompok Mahasiswa? - Sarah Afifah; Nabila Frasista Rahmadhania; Melani Cahyaningtyas (CV. Era Digital Nusantara, 2026)
This study aims to determine the relationship between achievement motivation and social loafing in students. The method used in this study is a quantitative correlational method, using the achievement motivation scale and the social loafing scale. Sampling in this study used a purposive sampling technique with a total of 110 students using the Achievement Motives Scale (AMS) and the Social Loafing Scale. The data analysis technique in this study was Pearson Correlation. Based on the results of the data analysis, the correlation coefficient (r) value was obtained at 0.372 with a significance value of p = 0.001 (p <0.05), this means that there is a relationship between achievement motivation and social loafing in students at UIN Raden Fatah Palembang. This means that Achievement Motivation can predict Social Loafing in student group assignments. Based on these findings, the results of this study provide implications for the importance of increasing student achievement motivation in order to reduce social loafing behavior.